Hip-abductor fatigue and single-leg landing mechanics in women athletes - Patrek, M. F.; Kernozek, T. W.; Willson, J. D.; Wright, G. A.; Doberstein, S. T. (Journal of Athletic Training, 2011)
Context: Reduced hip-abductor strength and muscle activation may be associated with altered lower extremity mechanics, which are thought to increase the risk for anterior cruciate ligament injury. However, experimental evidence supporting this relationship is limited.